Temporary shunt and carotid endarterectomy (review of literature) - A. N. Kazantsev; V. N. Kravchuk; R. A. Vinogradov; M. A. Chernyavsky; G. G. Khubulava (Вестник хирургии имени И.И. Грекова)
The main idea of this article is based on the uncertainty of the current recommendations, according to which a temporary shunt (TS) during carotid endarterectomy (CEE) can be used selectively, routinely, and even completely abandon its use. This statement is supported by the low level of evidence (class B) of the conclusion that indications for the use of TS are established only on the basis of a decrease in retrograde pressure in the internal carotid artery (ICA) and/or indicators of cerebral oximetry. Thus, the low efficiency of these procedures makes it possible not to use them at all.